Las digresiones del lenguaje, mea culpa, fastidium, dubitatio, y carnaval en La Florida del Inca Garcilaso de la Vega. - Moore, Charles B. (2012)
Although much has been written about el Inca Garcilaso de la Vega's Comentario reales, his chronicle about Hernando de Soto's adventure in the American southeast has never enjoyed the same reception. Be it for its supposed novelization of the adventure or for the far-away lands which it describes, the work has never been part of the colonial cannon. For that reason, this essay intends to study five classical digressions which el Inca may have used to embellish the work, impress his critics, and therefore, enhance his reputation as one of the greatest New World historians of his time.